Accurate segmentation of neonatal brain MRI with deep learning - Richter, Leonie; Fetit, Ahmed E. (Frontiers in Neuroinformatics, 2022)
An important step towards delivering an accurate connectome of the human brain is robust segmentation of 3D Magnetic Resonance Imaging (MRI) scans, which is particularly challenging when carried out on perinatal data. In this paper, we present an automated, deep learned-based pipeline for accurate segmentation of tissues from neonatal brain MRI, and extend it to carry out accurate age prediction. A major constraint to using deep learning techniques on developing brain data is the need to collect large numbers of ground truth labels. We therefore also investigate two practical approaches that can help alleviate the problem of label scarcity without loss of segmentation performance. First, we examine the efficiency of different strategies of distributing a limited budget of annotated 2D slices over 3D training images. In the second approach, we compare the segmentation performance of pre-trained models with different strategies of fine-tuning on a small subset of preterm infants. Our results indicate that distributing labels over a larger number of brain scans can improve segmentation performance. We also show that even partial fine-tuning can be superior in performance to a model trained from scratch, highlighting the relevance of transfer learning strategies under conditions of label scarcity. We illustrate our findings on large, publicly available T1- and T2-weighted MRI scans (n=709, range of ages at scan: 26-45 weeks) obtained retrospectively from the Developing Human Connectome Project cohort.